Family history of malignant or benign thyroid tumors: implications for surgical procedure management and disease-free survival - Jiang, Yu-jia; Han, Zhuo-jun; Hu, Yi-xuan; Zhang, Ning; Huang, Tao (Frontiers in Endocrinology, 2023)
Background: Current guidelines lack a standardized management for patients with family history of thyroid carcinoma (fTC),particularly benign thyroid neoplasm (fBTN). Our objective was to investigate the influence of various family histories on the selection of surgical approaches and disease-free survival (DFS).Methods: A cohort study was conducted involving 2261 patients diagnosed with differentiated thyroid carcinoma including those with fTC (n=224), fBTN (n=122), and individuals without a family history of thyroid carcinoma (nfTC; n=1915). Clinicopathological characteristics were collected. DFS was estimated using Kaplan-Meier analysis and factors affecting DFS were identified using Cox proportional hazard model.Results: Compared to nfTC, small tumor size, clinically lymph node-positive, extrathyroidal extension, vascular invasion, Hashimoto's disease and nodular goiter were more common in fTC and fBTN groups. They had lower T stage and a lower rate of good response to TSH suppression therapy but received more radioiodine therapy. It is worth noting that fTC is associated with male, bilateral and multifocal tumors, as well as central lymph node metastasis and distant metastasis. Both fTC (aHR = 2.45, 95% CI=1.11-5.38; P = 0.03) and fBTN (aHR = 3.43, 95% CI=1.27-9.29; P = 0.02) were independent predictors of DFS in patients who underwent lobectomy, but not total thyroidectomy. For 1-4 cm thyroid carcinomas with clinically node-negative, fTC was identified as an independent predictor, whereas fBTN was not.Our findings indicate that a family history, particularly of malignancy, is associated with a more aggressive disease. Family history does not affect the prognosis of patients who undergo total thyroidectomy, but it may increase the risk of postoperative malignant events in those who have a lobectomy. Additionally, it may be necessary to monitor individuals with a family history of benign thyroid neoplasms.